Three Phase Two-Arm Hybrid Active Filter Using Two Feedforward Loops with Self Tuning Filter for Elimination of 5th and 7th Harmonic Frequency (The International Journal of Engineering & Information Technology (IJEIT), 2024)
A novel topology for three-phase three-wire hybrid power filter with two-arm is proposed, this hybrid filter configured by a classical active filter consisting of two-arm bridge using two power electronic switches for each arm and two DC capacitors located in the DC side of the power converter, this topology uses less number of power electronic switches that allow to reduce the manufacturing cost. The active filter connected in series with a passive filter. The nonlinear load is a diode rectifier feeding a (R, C) parallel load. The proposed method is based on self-tuning filter placed in both feedback and feedforward loops dedicated to eliminate the 5th and 7th harmonics frequency. The feedforward loop consists in two branches, one to remove the 5th harmonic and the other one to remove 7th harmonic frequency. The use of self-tuning filter simplifies the control scheme by reducing the number of extraction filters, used in classical feedback and feedforward loops. More, in this case, no phase locked loop is necessary for the feedforward loop. The effectiveness of this new proposed scheme has been verified by computer simulation.